Cross-Country Perspective: Imposing Sanctions on Grab Partners with Invalid Identities in Indonesia and Singapore - Silviani, Ninne Zahara; Nurlaily; Vivi (Fakultas Hukum Universitas Hang Tuah, 2023)
Technology continues to advance as time evolves. Conventional transportation methods have long been the preferred choice for individuals heading to specific destinations. However, the emergence of online-based transportation services like Grab has made it easier for people to move around by simply using the GrabAppon their smartphones. While the GrabApphas brought numerous benefits to society it also comes with certain drawbacks, such as instances where drivers do not align their identities with the information provided on the Grab platform. This mismatch can lead to potential inconveniences and safety concerns for consumers, including the possibility of account takeovers. The objective of this research is to understand and analyze the consumer protection regulations concerning legal issues and forms of protection, and to undertake a comparative analysis of the legal frameworks in Indonesia and Singapore regarding online drivers and the penalties imposed when they encounter legal complications. In conducting this research, the author adopted a normative doctrinal research approach, encompassing legislative and comparative legal perspectives. The data gathered during this investigation were subjected to qualitative analysis techniques. The research findings reveal that the legal regulations in Indonesia and Singapore are relatively similar. Both countries have regulations covering traffic and transportation, consumer protection, and sanctions for drivers whose identities do not match the application. The result of the research is to improve the regulation concerning the implementation of sovereign rights and jurisdiction that is related regulatory provisions regarding consumer’s right in Indonesia and Singapore.